KEDUDUKAN HUKUM PARALEGAL DESA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 22P/HUM/2018 - Andrie Gusti Ari Sarjono (Magister Hukum Universitas HKBP Nommensen, 2020)
To eliminate or at least minimize the misuse of village funds, paralegal participation is needed. Paralegals are people who can optimize various opportunities to overcome the legal problems that exist in the village. Law Number 16 of 2011 concerning Legal Aid has given juridical legitimacy to the existence of a Paralegal as part of the legal aid provider. What is meant by legal aid is legal services provided by legal aid providers for free to legal aid recipients. Legal aid is provided by legal aid organizations or community organizations that provide legal aid services, which include exercising power of attorney, assisting, representing, defending, and / or carrying out other legal actions for the legal benefit of the recipient of legal aid. In its implementation, the legal aid provider is given the right to recruit lawyers, paralegal, lecturers, and students of the Faculty of Law. In the Judicial Review Decision, it was stated that the Paralegal did not carry out the advocate function but carried out the function of assisting lawyers. So the ability between Paralegals and Advocates is judged to be indeed far different and cannot be aligned. Paralegals should be grateful to Advocates and the Supreme Court for creating legal certainty over the functions of the Paralegal so that they do not collide with the functions of the Advocate profession and still maintain the position of the Paralegal in law in Indonesia. This Supreme Court ruling should be appreciated by all groups because it has achieved three legal objectives namely justice (gerechtigheit), expediency (zwechmaerten), and certainty (rechtssicherkeit.) As stated by a legal expert named Gustav Radburch.